Question
upstudy study bank question image url

\( \sum_{t=-2}^{30}(4 t+6) \) Evaluate

Ask by Martin Knight. in South Africa
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

The sum \( \sum_{t=-2}^{30} (4t + 6) \) equals 2046.

Solution

To evaluate the sum: \[ \sum_{t=-2}^{30} (4t + 6) \] Let's break it down step by step. ### 1. Identify the Number of Terms The summation starts at \( t = -2 \) and ends at \( t = 30 \). To find the number of terms: \[ \text{Number of terms} = 30 - (-2) + 1 = 33 \] ### 2. Determine the First and Last Terms - **First term (\( t = -2 \))**: \[ 4(-2) + 6 = -8 + 6 = -2 \] - **Last term (\( t = 30 \))**: \[ 4(30) + 6 = 120 + 6 = 126 \] ### 3. Use the Arithmetic Series Formula For an arithmetic series, the sum \( S \) is given by: \[ S = \frac{\text{Number of terms}}{2} \times (\text{First term} + \text{Last term}) \] Plugging in the values: \[ S = \frac{33}{2} \times (-2 + 126) = \frac{33}{2} \times 124 = 33 \times 62 = 2046 \] ### Alternative Verification Alternatively, separate the sum: \[ \sum_{t=-2}^{30} (4t + 6) = 4 \sum_{t=-2}^{30} t + \sum_{t=-2}^{30} 6 \] Calculate each part: - Sum of \( t \) from \( -2 \) to \( 30 \): \[ \frac{33}{2} \times ( -2 + 30 ) = \frac{33}{2} \times 28 = 33 \times 14 = 462 \] - Sum of 6 over 33 terms: \[ 6 \times 33 = 198 \] Combine them: \[ 4 \times 462 + 198 = 1848 + 198 = 2046 \] ### Final Answer \(\boxed{2046}\)

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Extra Insights

To evaluate the sum \( \sum_{t=-2}^{30}(4 t+6) \), we can start by simplifying the expression inside the summation: \[ 4t + 6 \] First, we will find the number of terms in the sum. The sum runs from \( t = -2 \) to \( t = 30 \). The number of terms is: \[ 30 - (-2) + 1 = 30 + 2 + 1 = 33 \] Next, we can express the sum of the linear expression. Decomposing the sum: \[ \sum_{t=-2}^{30} (4t + 6) = \sum_{t=-2}^{30} 4t + \sum_{t=-2}^{30} 6 \] The second sum is straightforward since there are 33 terms, each contributing 6: \[ \sum_{t=-2}^{30} 6 = 6 \times 33 = 198 \] Now we calculate the first sum \( \sum_{t=-2}^{30} 4t \): \[ \sum_{t=-2}^{30} 4t = 4 \sum_{t=-2}^{30} t \] To find \( \sum_{t=-2}^{30} t \), we use the formula for the sum of an arithmetic series: \[ \sum_{k=a}^{b} k = \frac{n}{2} (a+b) \] where \( n \) is the number of terms, \( a \) is the first term, and \( b \) is the last term. Here, \( a = -2 \), \( b = 30 \), and \( n = 33 \). Thus, \[ \sum_{t=-2}^{30} t = \frac{33}{2}((-2) + 30) = \frac{33}{2}(28) = 33 \times 14 = 462 \] Now we can return to the first sum: \[ \sum_{t=-2}^{30} 4t = 4 \cdot 462 = 1848 \] Combining both parts of the sum: \[ \sum_{t=-2}^{30} (4t + 6) = 1848 + 198 = 2046 \] Thus, the final answer is: \[ \boxed{2046} \]

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy